Nkx2.7 is a conserved regulator of craniofacial development - Caitlin Ford; Carmen de Sena-Tomás; Tint Tha Ra Wun; Angelika G. Aleman; Uday Rangaswamy; Jake Leyhr; María I. Nuñez; Cynthia Zehui Gao; Hieu T. Nim; Michael See; Ugo Coppola; Joshua S. Waxman; et al. (Nature Communications)
Abstract Craniofacial malformations arise from developmental defects in the head, face, and neck with phenotypes such as 22q11.2 deletion syndrome illustrating a developmental link between cardiovascular and craniofacial morphogenesis. NKX2-5 is a key cardiac transcription factor associated with congenital heart disease and mouse models of Nkx2-5 deficiency highlight roles in cardiac development. In zebrafish, nkx2.5 and nkx2.7 are paralogues in the NK4 family expressed in cardiomyocytes and pharyngeal arches. Despite shared cellular origins of cardiac and craniofacial tissues, the function of NK4 factors in head and neck patterning has not been elucidated. Molecular evolutionary analysis of NK4 genes shows that nkx2.5 and nkx2.7 are ohnologs resulting from whole genome duplication events. Nkx2.7 serves as a previously unappreciated regulator of branchiomeric muscle and cartilage formation for which nkx2.5 cannot fully compensate. Mechanistically, our results highlight that Nkx2.7 patterns the cranial neural crest and functions upstream of Endothelin1 to inhibit Notch signals. Together, our studies shed light on an evolutionarily conserved Nkx transcription factor with unique functions in vertebrate craniofacial development, advancing our understanding of congenital head and neck deformities.